Salmonella in domestic animals (CABI, 2000)
This book is written by leading researchers of Salmonella from Europe, North America and Australia. It provides an up-to-date review of work on all aspects of Salmonella in farm and companion animals, including characteristics and biology, virulence, effects on the host, antibacterial resistance, epidemiology, disease prevention and laboratory methods. This book is an essential reference for researches in animal science, veterinary medicine and microbiology and those working in the public health sector.